Survival analysis of hospitalized COVID-19 patients in New Yangon General Hospital by prognostic indicators - Htoo, Thant Syn; Lwin, Swe Mar Myint; Aung, May Soe; Nwe, Thin Thin (International Journal of Research in Medical Sciences, 2023)
Background: Coronavirus disease (COVID-19) is an infectious disease of the SARS-CoV-2 virus and it can infect anyone resulting in serious illness and death. Methods: A retrospective cohort study was conducted in New Yangon General Hospital (NYGH), Yangon between September and November, 2022. Previous records of COVID-19 in-patients admitted to NYGH from 1st June to 31st October, 2021, were reviewed. COVID-19 in-patients who tested positive by real-time reverse transcriptase-polymerase chain reaction (RT-PCR) or rapid diagnostic test (RDT) were included in this study. Multivariate analysis by Cox proportional-hazards (CPH) model was used to identify the prognostic indicators associated with the survival of COVID-19 inpatients. Results: Of (460) COVID-19 positive patients, there were 133 (28.9%) deaths with mortality rate of 16.9 per 1000 person-days. Then, 97 (72.9%) deaths occurred within 21 days of symptom onset, with median survival time of 28 (95% CI: 25-36) days. The results of the CPH model showed that the abnormal chest X-ray (CXR) [aHR=3.8, 95% CI: (1.1, 12.6), p=0.032], SpO2 level below 92% [aHR=3.7, 95% CI: 2.3, 5.9, p<0.001)], serum creatinine level more than 133 µmol/L [aHR=1.9, 95% CI: 1.1, 3.2, p=0.025] and C-reactive protein level (CRP) more than 10 mg/L [aHR=3.9, 95% CI: 1.2, 12.9, p=0.027] were the prognostic indicators of COVID-19 death among inpatients in NYGH. Conclusions: Patients with abnormal CXR result, low SpO2 level, high serum creatinine level, and high CRP level may have increased risks of death among COVID-19 inpatients in NYGH. Thus, close monitoring of the hospitalized COVID-19 inpatients by using these prognostic indicators should be emphasized.